The flagellar adenylate kinases of Trypanosoma cruzi - Camara, María de los Milagros (2015)
Adenylate kinases (ADK) are key enzymes involved in cell energy management. Trypanosomatids present the highest number of variants in a single cell in comparison with the rest of the living organisms. In this work, we characterized two flagellar ADKs from Trypanosoma cruzi, called TcADK1 and TcADK4, which are also located in the cell cytosol. Interestingly, TcADK1 presents a stage-specific expression. This variant was detected in epimastigotes cells, and was completely absent in trypomastigotes and amastigotes, while TcADK4 is present in the major life cycle stages of T. cruzi. Both variants are also regulated, in opposite ways, along the parasite growth curve suggesting that their expression depends on the intra- and extracellular conditions. Both, TcADK1 and TcADK4 present N-terminal extension that could be responsible for their subcellular localization. The presence of ADK variants in the flagellum would be critical for the provision of energy in a process of high ATP consumption such as cell motility.